Response of the Bacterial Communities Associated With Maize Rhizosphere to Poultry Litter as an Organomineral Fertilizer - Vollú, Renata Estebanez; Cotta, Simone Raposo; Jurelevicius, Diogo; Leite, Deborah Catharine de Assis; Parente, Cláudio Ernesto Taveira; Malm, Olaf; Martins, Denize Carvalho; Resende, Álvaro Vilela; Marriel, Ivanildo Evódio; Seldin, Lucy (Frontiers in Environmental Science, 2018)
Maize is an important food source worldwide and is of considerable industrial importance. Low maize yields are mostly due to low soil fertility, so expensive mineral fertilizers are often used to offset the lack of nutrients. Poultry litter (PL) is one of the most valuable and phosphorous-rich animal wastes. However, PL usually contains veterinary antibiotic residues, particularly fluoroquinolones (FQs), which may alter soil microorganism diversity and resistance patterns. In this study, we aimed to understand the impact of applying mineral (triple superphosphate - STP) or organomineral (STP with PL and reactive Bayovar phosphate with PL) fertilizers (130 or 260 kg/ha of total P2O5) on the structure and composition of the soil bacteriome and on phosphate-mineralizing bacteria associated with the maize rhizosphere. Maize plants were sampled at 60 and 90 days after sowing and a clear rhizosphere effect was observed in all samples. No specific groups of bacterial genera predominated (>3% relative abundance) according to the different fertilizer treatments and most of the genera were shared among samples. Multivariate analyses of 16S rRNA sequences revealed clear clustering based on sampling time and distinct separation from bulk soil samples. Abundances of phosphate-mineralizing bacteria varied depending on the sampling time. We observed a positive effect on phytase activity under the 260 kg STP with PL treatment. Although the FQ enrofloxacin and its main metabolite ciprofloxacin were detected in PL, their concentrations in fertilized soils were below quantification thresholds. Quinolone resistance genes were not detected in the maize rhizosphere or bulk soil. Together, these results suggest that the rhizosphere effect, plant age and applied amounts of fertilizer are more influential on bacterial communities than the type of fertilizer used. Thus, application of PL as an organomineral fertilizer does not appear to have extensive impacts on the bacterial diversity of maize rhizosphere, so it could be an excellent option for enhancing maize production.